Ninja innovation : the ten killer strategies of the world's most successful businesses - Shapiro, Gary (William Morrow, 2013)
The leader of the Consumer Electronics Association draws on his decades of experience working with the world's most innovative companies to reveal why success depends on following the ninja credo: creating a "killer strategy" with defined goals, flexibility, and a focus on innovative thinking.